Gray-code TDC with improved linearity and scalability for LiDAR applications - Machado, Rui (2020)
This paper presents a TDC architecture based on a gray code oscillator with improved linearity, for FPGA implementations. The proposed architecture introduces manual routing as a method to improve the TDC linearity and precision, by controlling the gray code oscillator Datapath, which also reduces the need for calibration mechanisms. Furthermore, the proposed manual routing procedure improves the performance homogeneity across multiple TDC channels, enabling the use of the same calibration module across multiple channels, if further improved precision is required. The proposed TDC channel uses only 16 FPGA logic resources (considering the Xilinx 7 series platform), making it suitable for applications where a large number of measurement channels are required. To validate the proposed architecture and routing procedure, two channels were integrated with a coarse counter, a FIFO memory and an AXI interface, to assemble the pulse measurement unit. A comparison between the default routing implementation and the proposed manual routing has been performed, shown an improvement of 27% on the overall TDC single-shot precision. The implemented TDC achieved a 380 ps RMS resolution, a maximum DNL of 0.38 LSB and a peak-to-peak INL of 0.69 LSB, corresponding to a 21.7% and 70.4% improvement, respectively, when compared to the default design approach.